Cobb Douglas Production Function Analysis of Cabbage (Brassica Oleracea Var. Capitata L) Farm at Desa Netpala, Kecamatan Mollo Utara, Kabupaten Timor Tengah Selatan - Nenda Teftae; Marthen Robinson Pellokila; Leta Rafael Levis (Undana Press, 2022)
This study aimed to find out the; 1) Conditions of return to scale cabbage vegetable farming, 2) The farmers’ income earning by selling cabbage in Netpala village, Mollo Utara sub- district of Timor Tengah Selatan regency. Netpala village was chosen as the location of the study using purposive sampling technique. Data collection was conducted in August 2019 and data was statisticaly descriptive analysis. The measured variable were the condition of retr’n to scale cabbage vegetable farming, and the amount of cabbage vegetable farming income (Rp). The results showed that 1) Cabbage vegetable farming in Netpala Village when viewed from the scale of results was in a condition of decreasing Return to Scale α + β <1 means that the proportion of the addition of production factors will produce additional production with a smaller proportion. The analysis shows that the parameters b + c + d + e = 0.960 are smaller than 1. This means that the proportion of the addition of production factors (inputs) in this case X1 (land area), X2 (seeds), X3 (fertilizer), X4 (power work) proportionally by 1% will result in an increase in Y (cabbage production) by 0.960%. 2) Cabbage vegetable farmers’ income in study site was Rp. 637,649,582 with the average income earned by the respondent amounting to Rp.12,031,124.